(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تلعب مشاركة الأفراد في سوق الأوراق المالية دوراً هاماً في تنمية وتطوير السوق المالية, في غياب مشاركة فعالة ومستمرة ونشطة تفتقر السوق المالية إلى المنتجات المالية وإلى الـسيولة, كما تؤدي زيادة المشاركة إلى خلق ديناميكية التداول الفعال بيعاً وشراءً. يدرس هذا البحث أثر المعرفة المالية على مشاركة الأفراد في سوق دمشق للأوراق المالية. لتحقيق هدف البحث جمعت البيانات بالاعتماد على استبانة صممت خصيصاً لهذا الغرض, وزعت الاستبانة على عينة مكونة من (384) فرداً من التجار والصناعيين المسجلين في غرفة تجارة دمشق وغرفة صناعة دمشق وريفها. استُخدم برنامج الحزمة الإحصائية للعلوم الاجتماعيةStatistical Package for Science المعروف اختصاراً SPSS في تحليل بيانات البحث. كما استُخدم مجموعة من الأساليب الإحصائية كالتكرارات والنسب المئوية, واختبار كاي مربع (Chi-Square Test) لاختبار فرضيات الدراسة المتعلقة بالعلاقة بين المتغيرات الديموغرافية والمعرفة المالية, إضافةً إلى نموذج الانحدار اللوجستي ((Logistic Regression لدراسة أثر المعرفة المالية على مشاركة الأفراد في سوق دمشق للأوراق المالية. توصل البحث إلى أن المعرفة المالية للأفراد المبحوثين بعيدة جداً عن المستوى المطلوب للمشاركة في سوق دمشق للأوراق المالية، حيث أن (22.1%) فقط من أفراد العينة يمتلكون مستوى جيد من المعرفة المالية. كما توصل البحث إلى وجود أثر ذو دلالة إحصائية للمعرفة المالية على المشاركة في سوق الأوراق المالية, فزيادة مؤشر المعرفة المالية من مستوى متدنٍ إلى مستوى جيد يؤدي إلى زيادة احتمال المشاركة بمقدار (24%). أيضاً توصل البحث إلى وجود علاقة بين كل من متغيري الجنس والدخل من جهة والمعرفة المالية من جهة أخرى, وعدم وجود علاقة بين المؤهل العلمي والمعرفة المالية. The individuals’ Participation in the Securities Exchange plays an important role in the development of the financial market. Without the active and continuous participation, the financial market lacks the financial products and its liquidity, and also the increased participation leads to the creation of effective trading dynamics of buying and selling. This paper examines the impact of financial literacy on the individuals’ Participation in Damascus Securities Exchange. To achieve the objective of the study, data is collected based on a questionnaire specially designed for this purpose. And the questionnaire has been distributed to a sample of (384) individuals from the merchants and industrialists who are registered in the Damascus Chamber of Commerce and Damascus Chamber of Industry. The study to analysis data depends on using a software of Statistical Package for the Social Sciences known as SPSS. It has been used some statistical methods like repetition and percentages in addition to Chi-Square Test to examine hypotheses concerning the relationship between demographic variables and financial literacy, and a model logistic regression to study the impact of financial literacy on the individuals’s participation in the Damascus Securities Exchange The research finds that the financial literacy of the members of the respondents is very far from the desired level to participation in the Damascus Securities Exchange where only (22%) of respondents have a good level of financial literacy. In addition to that, the research highlights the presence of a statistically significant effect of financial literacy to participate in the securities exchange; the increasing financial literacy index from a low level to a better one leads to increase the likelihood of participation by (24%). The research also concludes two things that there is a relationship between each of the variables of gender, income and financial literacy, and on the other hand there is no relationship between the educational qualification and the financial literacy.